Advertising Regulations in Consumer Protection Law (Comparison of Consumer Protection Law in Indonesia and Thailand) - Putri, Juanita Tiffany (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Advertising not only increases the level of sales of a product, but also serves as an informative tool for consumers. The magnitude of the influence exerted means that a legal regulation is needed for advertising in order to create a conducive system between business actors and consumers. This research uses a normative juridical method by comparing Indonesian consumer protection legal regulations with the Consumer Protection Acr, B.E. 2522 Thailand. There are differences in advertising regulations in Indonesia based on UUPK and CPA, namely regarding the form of advertising prohibition by perpetrators and the sanctions given. The UUPK strictly regulates the prohibition of advertising an item using excessive and incorrect words. This is different from article 22 of the CPA which still provides room for business actors to creatively create advertisements that can attract consumers. Regarding the sanctions given, non-compliance by business actors with UUPK will result in a ban on trade by business actors. In contrast to the CPA, where if a business actor does not fulfill the provisions as stipulated regarding advertising, the CPA does not prohibit the business actor from stopping the trading activities or promotional efforts that are currently being carried out. However, CPA provides relief for business actors by requiring business actors to correct the use of these advertisements.